Investigation of the growth of particles produced in a laval nozzle - Zhalehrajabi, E. (Bellwether Publishing, Ltd., 2014)
This study focuses on numerical modeling of condensation of water vapor in a Laval nozzle, using the liquid drop nucleation theory. Influence of nozzle geometry, pressure, and temperature on the average drop size is reported. A computer program written in MATLAB was used used to calculate the nucleation and condensation of water vapor in the nozzle. The simulation results are validated with the available experimental data in the literature for steam condensation. The model reveals that the average drop size is reduced by increasing the divergent angle of the nozzle. The results also confirm that increasing the inlet pressure has a direct effect on the average drop size while temperature rise has an inverse effect on the drop size. Â© 2014 Copyright Taylor & Francis Group, LLC.